(untitled) (MAUSAM, 1970)
Vertical motion is an important parameter in any study of the atmospheric process. Evaluation of this parameter from derived values of divergence and vorticity involve elaborate calculations. A simple and quick method by adapting the vorticity equation in a simplified form has been attempted in the present study. The method has been applied to a small area formed by formed by four pibal stations in Gujarat. Vertical velocity for six layers between surface and 700 mb were calculated. With these values rainfall over the area was also computed and compared with the actual observed rainfall. The results are compared and discussed.